EFFECT OF LASER RADIATION ON TUMORS IN THE EXPERIMENT - N. O. Sodikov; Z. A. Muminova (European Science Publishing, 2025)
The current task facing medical science and practical health care of our time is the fight against the most dangerous disease of humanity - malignant tumors. Many researchers of various specialties in many countries of the world are working on this problem. Various radiation sources have long been used to treat malignant tumors. The invention of optical quantum generators (lasers) is one of the most significant and promising discoveries of the second half of the twentieth century. Therefore, it is quite natural that the emergence of a new type of radiation - radiation from optical quantum generators (lasers) - has not gone unnoticed.
Keywords: Laser, monochromaticity, density, radiation power, energy illumination, radiation dose, irradiation time, melanoma, anesthesia, dissemination.